2009
DOI: 10.1097/htr.0b013e3181a7ecd8
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions About Traumatic Brain Injury and Recovery Among Nursing Students

Abstract: Nursing students possess several misconceptions pertaining to TBI and recovery that have the potential to adversely affect assessment, treatment, and education of patients and family members. Education focusing on TBI and recovery should be included in the nursing curriculum and be a part of continuing education at the professional level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 7 publications
6
37
2
Order By: Relevance
“…Generally, these findings appear to be comparable to the findings of Hux et al [1] and Chapman and Hudson, [15] which also indicated misconception rates ranging from 43.8% to 60.6% for amnesia and 54.7% to 63.4% for unconciousness, and that these 2 categories bore the most misconceptions. Participants had the fewest misconceptions in the brain damage category (8.4%), which is similar to the findings of Hux et al [1] (8.3%) and Ernst et al [13] (6.6%). Generally, these findings are in keeping with previous literature, which suggests that misconceptions about TBIs are common among the general population.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Generally, these findings appear to be comparable to the findings of Hux et al [1] and Chapman and Hudson, [15] which also indicated misconception rates ranging from 43.8% to 60.6% for amnesia and 54.7% to 63.4% for unconciousness, and that these 2 categories bore the most misconceptions. Participants had the fewest misconceptions in the brain damage category (8.4%), which is similar to the findings of Hux et al [1] (8.3%) and Ernst et al [13] (6.6%). Generally, these findings are in keeping with previous literature, which suggests that misconceptions about TBIs are common among the general population.…”
Section: Discussionsupporting
confidence: 81%
“…[9] A large number of participants appear to believe that a person with a brain injury may have trouble remembering events that happened before the injury, but usually does not have trouble learning new things (62.1% v. 49.8% -79.3% in previous studies). [1,9,13,14] Furthermore, a substantial number seemed to believe that people who have had 1 brain injury are not more likely to have a second one (70% v. 71.3% to 83.4% in previous studies). [11,13,14] Finally, 88% of the participants seemed to believe that individuals with a brain injury can forget who they are and not recognise others, but be normal in every other way (v. 82.35% -93.4% in previous studies).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations